Legal Protection for Victims of Business Email Compromise Crimes - Lie, Laksana Budiwiyono (IHSA Institute, 2024)
Business Email Compromise (BEC) is increasingly rampant in Indonesia, with significant impacts on financial losses and data security. This cybercrime exploits weaknesses in email systems and the lack of vigilance among companies to steal sensitive information. This research uses normative juridical methods and literature study to analyze the applicable legal framework, law enforcement processes, and protection efforts for BEC victims. The research results show that although Law Number 11 of 2008 concerning Information and Electronic Transactions (ITE Law) and Law Number 27 of 2022 concerning Personal Data Protection (PDP Law) provide a legal basis, both have limitations in specifically addressing BEC. Law enforcement faces challenges in terms of digital evidence and perpetrators who often operate abroad. To enhance legal protection for victims, it is recommended to revise regulations, strengthen law enforcement capacities, and undertake prevention efforts through public education and cooperation with the private sector